ANALISIS PENERAPAN ENTERPRISE RISK MANAJEMEN PADA PERUSAHAAN JASA PENGIRIMAN BARANG PT. MERPATI ALAM SEMESTA BERDASARKAN COSO – ENTERPRISE RISK MANAGEMENT INTEGRATED FRAMEWORK - Kurnia Syahlan; Novita Novita (Universitas Trilogi, 2025)
This study aims to analyze the application of ERM at PT. Merpati Alam Semesta (MAS), a courier service company, using the COSO Enterprise Risk Management Integrated Framework. This research employs a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis. The results indicate that PT. MAS has comprehensively implemented the COSO ERM components, evidenced by strong top-management commitment (tone at the top), internalized integrity and ethics, a clear organizational structure, and the integration of ERM with the ISO 9001:2015 quality management system. The company successfully identifies, assesses, and responds to operational and strategic risks while leveraging innovation opportunities. Challenges include the socialization of risk appetite, resistance to SOP updates, and the complexity of risk correlation modeling. Practical implications of this study include recommendations to enhance ERM effectiveness through risk dashboard visualization, system automation, predictive technology utilization, and strengthening whistleblowing channels.Keywords: Enterprise Risk Management, COSO ERM, risk management, courier service company, ISO 9001.